Planning and budgeting process in the security sector of the Republic of North Macedonia - Bakreski, Oliver; Cvetkovski, Sergej; Bardjieva Miovska, Leta (International Institute of Social and Economic Sciences, 2021)
This paper aims to present the planning process in the security sector, which is complex, intricate, multi-phase and dynamic and is based on the design of budget requirements for the needs of the security sector. Planning counterpoises an activity in the creation of government draft budgets, which has a significant impact on the execution of budget projections. Hence, planning in the security sector is of great importance in providing the architecture of contemporary budgeting, setting and prioritizing goals and creating security policies. The initial premise in this paper refers to the hypothesis that planning is an essential element of security sector management and addresses the need for continuity in strategic and comprehensive planning in order to prepare and approve a budget that comprises the real needs of the security sector, as well as the necessity of implementation of the principles of cost effectiveness, budget transparency, system of control and balance and democratic oversight of budget implementation. The dependent variable in the context of this hypothesis alludes to the assessment of security risks and threats, the environment, etc., which is in function of achieving the planned goals based on a specific time frame, clear organizational designation and system of accountability. The methodology for this paper includes extrapolation, qualitative presentation and concrete interpretation of theoretical and empirical findings and available data on the specific topic through induction and deduction, analysis of formal government documents, strategies and plans, as well as laws governing this domain. The purpose of this paper is to emphasize the importance of planning as an initial stage in budgeting and the end result of the security resource planning process.
Keywords: planning, goals, security, defense, resources, budgeting process